HUBUNGAN PENGELOLAAN LAHAN PERSAWAHAN DAN LUAS LAHAN DENGAN TINGKAT PRODUKSI PADI SAWAH DI KENAGARAIAN KOTO GAEK GUGUK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Sofia, Ega Windra (Pendidikan Geografi, 2014)
Management of paddy fields has not been good or not as expected and the less land area , as a result , directly or indirectly related to the level of rice production in Koto Kenagarian Gaek Guguk Gunung Talang District of Solok . This study aimed to determine the relationship of land management and land with paddy rice production levels in Kenagarian Koto Gaek Guguk Gunung Talang District of Solok . Type is classified as descriptive correlational study that aims to find the correlation of independent variables with the dependent variable . Population is taken in this research that the whole community living in Koto Kenagarian Gaek Guguk Mount Talang District of Solok district , which livelihood as rice farmers , amounting to as many as 389 households. The sampling technique used is proportional random sampling , where for every family farm taken with a proportion of 20% , then the sample size in this study amounted to 77 households. The results of this study indicate that : 1) there is a significant relationship between the management of paddy fields with rice production levels in Kenagarian Koto Gaek Guguk Gunung Talang Solok district , with a low contribution ( r = 0.252 ) and the contributions made by 6.3 % , 2 ) there is a significant relationship between the level of the land area with rice production in Koto Kenagarian Gaek Guguk Mount Talang District of Solok district , with the contribution being ( r = 0.419 ) and the contributions made by 17.6 % , 3 ) there is a relationship management of paddy fields and the land together with the level of rice production in Koto Kenagarian Gaek Guguk Gunung Talang Solok district , with the contribution being ( r = 0.459 ) and the contributions made by 21 % .